Turbulent magnetic energy spectrum and the cancellation function of solar photospheric magnetic fields. Issue 9 (November 2013) - Marschalkó, G.; Petrovay, K.; Barnaföldi, Gergely Gábor; Forgás‐Dajka, Emese; Kiss, Csaba; Verebélyi, Erika
Abstract A simple analytical relation of form α = 2κ – 1 between the magnetic energy spectral exponent α of the turbulent magnetic field in the solar photosphere and its magnetic flux cancellation exponent κ, valid under certain restrictive assumptions, is tested and extended outside its range of validity in a series of Monte Carlo simulations. In these numerical tests artificial "magnetograms" are constructed in 1D and 2D by superposing a discrete set of Fourier modes of the magnetic field distribution with amplitudes following a power law spectrum and measuring the cancellation function on these simulated magnetograms. Our results confirm the validity of the analytical relation and extend it to the domain α < –1 where κ → 0 as α → –∞. The observationally derived upper limit of 0.38 on κ implies α < –0.24 in the granular size range, apparently at odds with a small scale dynamo driven in the inertial range. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)